Shield ulcer in keratoconus in the absence of atopic or vernal kerato-conjunctivitis - Niestrata, Magdalena; Kohli, Shuchi; Saleki, Mohammad; Ashena, Zahra (GMS Ophthalmology Cases)
Corneal shield ulcer is a severe complication of atopic keratoconjunctivitis (AKC) and vernal keratoconjunctivitis (VKC). This condition is caused by the mechanical irritation of the corneal epithelium due to giant papillae and toxic epitheliopathy resulting from inflammatory mediators. To date, there have been no reported cases of corneal shield ulcers in the literature without AKC or VKC. However, the authors have reported a unique case of shield ulcer in a patient with keratoconus but no history of AKC or VKC. The cause is hypothesised to be due to mechanical friction between the corneal steep apex and palpebral conjunctiva. Additionally, a new technique, the use of a dry amniotic membrane, is described to manage the persistent epithelial defect in shield ulcers.